RESULTS OF THE ANALYSIS OF PROFITABILITY AND THE BUSINESS SUCCESS OF COMPANIES FROM THE SECTOR OF ACCOMMODATION AND CATERING SERVICES IN THE REPUBLIC OF SERBIA - Filipović, Vesna; Nikica, Radović (The Business of Tourism, 2024)
The analysis of the success of business operations of companies is generally carried out by applying models that are formed from several ratio numbers, and aims at the possibility of reviewing the achieved results, but also possible assessment of problems in future operations. The subject of the research in this paper is the analysis of profitability indicators and evaluation of business success of companies that operate in the sector of Accommodation and food services in the Republic of Serbia. Based on data from the Annual Bulletin of Financial Reports downloaded from the website of the Agency for Business Registers (in text ABR) for the years 2022 and 2023 on the results of business operations of companies in the sector of Accommodation and catering services in the Republic of Serbia, profitability indicators were analyzed using Kralicek's QuickTest the success of the business was analyzed and a forecast of the business stability of the analyzed companies was given. Based on the obtained results of profitability indicators, the business situation of a large number of companies from the Accommodation and catering services sector, which in 2019 and 2020 business year, due to positive trends in the tourism market, strategically invested in business improvement, but in 2020 and 2021 , due to the crisis caused by the COVID-19 pandemic, had poor business results, is confirmed. Changes in the tourist market in 2022 and 2023 lead to an increase in the business results of the analyzed companies, so it is expected that the mentioned strategic investments will become profitable, already in 2024, for which the results of tourist traffic in the Republic of Serbia indicate an increase in the business income of companies of the analyzed sector.
Keywords: profitability, business success, Kralicek's QuickTest, hotel industry, restaurant business